LITERARY HISTORY CONCEPTIONS OF B. LEPKY - KHOROB , STEPAN (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article addresses the issue of the methodological conceptualism developed by Ukrainian literary historian Bohdan Lepky. The analysis proves that his textbook Nacherk istorii ukrainskoi literatury (An Essay on the History of Ukrainian Literature) retains its literary value and its place among the textbooks and study guides published in the first half of the 20th century.